1990
DOI: 10.1159/000235114
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of Mast-Cell-Bound IgE Idiotypes with Anti-Idiotypic Antibody: Mediator Release or Inhibition of Antigen-Induced Mediator Release?

Abstract: When anti-idiotypic antibodies specific for idiotopes on IgE antibodies react with mast-dell-bound IgE antibody, the reaction may be expected to lead either to mediator release or to inhibition of allergen-induced release. This study was carried out to determine which would occur. Anti-idiotype antiserum (anti-Ids) was raised in syngeneic mice by immunisation with affinity-purified DNP-specific mouse monoclonal IgE. Sera from these immunised mice and from a similarly immunised rabbit inhibited the binding of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 5 publications
(5 reference statements)
0
4
0
Order By: Relevance
“…4C). Furthermore, successful immunotherapy was considered to rely on continuous anti-id targeting of the mast cells rendering internalization and, therefore, depletion of cell bound specific IgE 28…”
Section: The Functional Role Of Anti-ids In Allergymentioning
confidence: 99%
“…4C). Furthermore, successful immunotherapy was considered to rely on continuous anti-id targeting of the mast cells rendering internalization and, therefore, depletion of cell bound specific IgE 28…”
Section: The Functional Role Of Anti-ids In Allergymentioning
confidence: 99%
“…Do anti-Id antibodies have a role in triggering histamine release from basophils and mastocytes or do tliey have the capacity to block the allergen-induced histamine release, besides of course iheir potential to regulate the production of antibodies carrying the corresponding idiotypes? This question has already been debated [17]. The protection ofthe allergen binding site by paratope-speclfic anti-Ids would be beneficial if IgE is linked to anti-Ids without extensive basophil degranulation and indeed the above-mentioned reasons make anti-Id antibodies good candidates as weak degranulators.…”
Section: Discussionmentioning
confidence: 99%
“…Of particular interest in this regard is the capacity of anti-Ids to specifically recognize Ids carried by IgE antibodies [16]. Interaction with IgE antibodies located at the surface of a basophil or mastocyte could indeed result in two types of effects: crosslinkiniz of IgE molecules and degranulation of the cell, or inhibition of allergen-dependent degranuiation [17], Deciding which of these two phenomena would predominate is of obvious importance for our understanding of how anti-Ids act physiologically, but also for the design of therapies whose aim would be to increase the production of anti-Ids [IS], Anti-!ds raised in animals can recognize Ids carried by surface-bound IgE, Thus, mouse anti-Ids can induce a passive cutaneous anaphylactic response and release of mediators from IgE-sensiti/ed rat mast cells [17], Rabbit polyclonal and murine monoclonal anti-Ids have been shown to interact with human IgE on the hasophil surface, resulting in histamine release [19.20]. However, whether human anti-Ids could interact with human IgE on basophils has never been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Two possible mecha nisms haven been suggested to account for the desensitiz ing effect of auto-anti-idiotype antibodies. As anti-idio type antibodies mimic the allergen they were believed to inhibit binding of allergen to mast cell bound specific IgE without being able to induce mast cell degranulation, how ever several groups found that anti-idiotype antibodies can induce histamine release from mast cells [7,8], Anoth er mechanism explains the desensitizing effect of anti-idi otype antibodies by depletion of cell-bound IgE by contin uous triggering of the mast cells by subsymptomatic doses of these antibodies. This type of immunotherapy is more likely to be successful!…”
Section: Introductionmentioning
confidence: 99%